Identities, Power, And ¨Political Incidence Of Organizations Linked To Nicaraguan Immigrants In Costa Rica: Theoretical And Methodological Contributions. - Mojica-Mendieta, Francisco Javier (2009)
From a critical and propositive perspective, the author proposes theoretical and methodological contributions for the understanding of national identities and their articulation with the political incidence of different organized social actors linked to Nicaraguan immigrants in Costa Rica. He suggests that the study of identities, and more specifically, of national identities, is incomplete without addressing the exercise of power and the political influence of agents in the vindication of the human rights of migrant populations.